Photovoltaic Properties of Films of Polyvinyl Alcohol–Xanthene Dye Composites - Afanas’ev, D. A.; Davidenko, N. A.; Davidenko, I. I.; Ibraev, N. Kh.; Mokrinskaya, E. V.; Studzinskii, S. L.; Pavlov, V. A.; Tonkopieva, L. S.; Chuprina, N. G. (MAIK NAUKA/INTERPERIODICA/SPRINGER, 233 SPRING ST, NEW YORK, 2015)
It has been found that films of polymer composites based on polyvinyl alcohol doped with a xan thene dye possess photovoltaic properties, and the photovoltaic response varies little at the dye concentration greater than 10 wt % with respect to the weight of the polymer. The photovoltaic effect is due to photogeneration of charge carriers in the dye aggregates and transport of nonequilibrium charge carriers among them. It is concluded that, in order to reduce the production cost of photoactive media for photovoltaic cells, it is possible to use cheap polymers with a low concentration of organic dyes.